Morning peak period travel characteristics of a residential suburb in Cape Town during a school and holiday period : what lessons can we learn? - Hermant, Laurent Fernand Leon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2008.